Introduction of an interprofessional gynaecology surgical skills workshop for undergraduate medical and nursing students. (24th October 2019) - Yang, Amy; Fernando, Shavi; Tighe, Josie; O‐Halloran, Monica; Morphet, Julia; Kumar, Arunaz
Abstract : Background: Medical and nursing students may feel under‐prepared to perform basic surgical and gynaecology procedural skills. There also remains scope within undergraduate programs to integrate interprofessional education, and better prepare students for interprofessional collaboration to improve patient care. Aims: A simulation‐based gynaecology surgical skills workshop program was introduced for undergraduate medical and nursing students. The aim of this study was to explore students' perceptions of a simulation‐based interprofessional gynaecological skills program, using students' pre‐ and post‐workshop confidence in taught skills reported in a post‐workshop questionnaire as an outcome measure. Materials and methods: One hundred and sixty undergraduate medical ( n  = 133) and nursing ( n  = 27) students attended the workshop program at a tertiary university in Melbourne, Australia. A survey was completed by all students immediately after the workshop, addressing students' perceptions of surgical education, the four skill‐stations (gowning/gloving, suturing, intrauterine device insertion, and urethral catheterisation), and interprofessional education. A Wilcoxon signed‐rank test was performed to compare students' pre‐ and post‐workshop confidence scores. Results: Most medical and nursing students (86%) agreed their course should provide more structured surgical education. There was a statistically significant increase in post‐workshop self‐reported confidence scores for medical and nursing students in all four taught skills. Confidence in interprofessional behaviours also improved in both cohorts, but the improvement in nursing students did not reach statistical significance. Conclusions: Simulation‐based, interprofessional, gynaecological surgery skills workshops are practical and valuable additions to undergraduate medical and nursing curricula. Further research should explore long‐term retention of procedural skills and changes in interprofessional attitudes in clinical practice.